(untitled) (Al-Academy, 2023)
Fashion design - like other arts - has been affected by different artistic trends, and has developed and devoted to it scientific and technical studies and experts specialized in new standards in the concept of design in line with the technical foundations followed in modern schools, including optical illusion This art appeared in the late thirties of the twentieth century, where its deep roots appeared in the Bauhaus School, one of the greatest art schools and has been interested in arts and architecture, and this school was founded in 1919 in Weimar, Germany, by Walter Gropius, and with At the beginning of the forties, several scattered models of visual art appeared, including visual effects, and in the early fifties, the art of optical illusion appeared as a distinct style. The school of optical illusion is one of the important art schools that play a prominent role in the design of fabrics and fashion, as the Cambridge Dictionary defines optical illusion as something that deceives the eye and makes a person think that he sees something that does not exist or sees it differently from reality, so the image appears to the seer in his mind and then reflected on the mirror of the eye in a way that changes his reality, so many fashion designers rely on deceiving the mind by using different patterns by following the methods of optical deception in m